2014
DOI: 10.1371/journal.pone.0113955
|View full text |Cite|
|
Sign up to set email alerts
|

G-Quadruplex Structures and CpG Methylation Cause Drop-Out of the Maternal Allele in Polymerase Chain Reaction Amplification of the Imprinted MEST Gene Promoter

Abstract: We observed apparent non-Mendelian behaviour of alleles when genotyping a region in a CpG island at the 5′ end of the maternally imprinted human MEST isoform. This region contains three single nucleotide polymorphisms (SNPs) in total linkage disequilibrium, such that only two haplotypes occur in the human population. Only one haplotype was detectable in each subject, never both, despite the use of multiple primers and several genotyping methods. We observed that this region contains motifs capable of forming s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 41 publications
3
59
2
Order By: Relevance
“…All three motifs had high thermal stability and displayed characteristics of G4 formation, however, methylation appeared to decrease the G4 stability as measured by CD, which was contrary to our initial hypothesis [19]. It is unclear how cytosine methylation impacts on G4 formation or stability, but this analysis showed that both factors were required to cause ADO and neither G4 formation or DNA methylation in isolation was sufficient.…”
Section: Introductioncontrasting
confidence: 84%
See 3 more Smart Citations
“…All three motifs had high thermal stability and displayed characteristics of G4 formation, however, methylation appeared to decrease the G4 stability as measured by CD, which was contrary to our initial hypothesis [19]. It is unclear how cytosine methylation impacts on G4 formation or stability, but this analysis showed that both factors were required to cause ADO and neither G4 formation or DNA methylation in isolation was sufficient.…”
Section: Introductioncontrasting
confidence: 84%
“…(2014) [19]. Non B-DNA formation was characterised using fluorescence analysis of dimethyl sulfate footprinting assay (FADFA) and fluorescence analysis of nuclease footprinting assay (FANFA), as previously described by Stevens et al .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…G4 motifs are enriched at the TSS, the 5′-UTR, and the 5′ end of the first intron and depleted in coding regions (Maizels and Gray 2013). In the promoters of several eukaryotic and prokaryotic genes, G-rich sequences with potential to form G4 have been identified (Rankin et al 2005;Rawal et al 2006;Stevens et al 2014). The potential for G4 structures to inhibit DNA synthesis has long been recognized (Han et al 1999;Boán et al 2004), as has its ability to act as a transcriptional repressor (Siddiqui-Jain et al 2002;Lin et al 2013).…”
Section: Introductionmentioning
confidence: 99%